Assessment of the relationship between the type of motivation to study and the sense of generalized self-efficacy among nursing students - Ziemiańska, Joanna; Krawczyk, Bożena (Journal of Education, Health and Sport, 2026)
Introduction The choice of a field of study is one of the key moments in a person’s life, determining not only their future professional career but also shaping their personal and social identity as well as their position in the labor market. Motivation plays a significant role in educational and career decision-making, particularly with regard to choosing a nursing career path, which involves high social responsibility and specific psychological and emotional demands. Aim of the Study The aim of the study was to assess the relationship between the type of motivation for studying and the level of generalized self-efficacy among nursing students. Material and Methods The study included 238 undergraduate nursing students from the Faculty of Health Sciences at the University of Bielsko-Biala. The research was conducted between November 2024 and January 2025. Data were collected using the diagnostic survey method with an original questionnaire and standardized research tools: the Academic Motivation Scale (AMS) and the Generalized Self-Efficacy Scale (GSES). Results The most frequently indicated type of motivation among nursing students was “external motivation – identified regulation” (mean = 5.72), followed by “external motivation – external regulation” (mean = 5.3) and “intrinsic motivation – to know” (mean = 5.3). The study group demonstrated a high level of generalized self-efficacy (mean ± SD: 31.98 ± 4.37). A high level was observed in 73.11% of participants, a moderate level in 23.11%, and a low level in only 3.78% of students. Conclusions The decision to undertake nursing studies among students of the University of Bielsko-Biala was mainly based on external motivation—identified and external regulation—as well as intrinsic motivation resulting from the need for knowledge. A significant relationship was found between the type of motivation and the level of self-efficacy.